2022
DOI: 10.1111/ina.13009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of improved indoor air quality in Nunavik homes on children’s respiratory health

Abstract: Between 2007 and 2012, hospitalization rate related to respiratory system diseases in children ≤1–year‐old was near 7 times higher in Nunavik compared with the whole province of Quebec. To assess the impact of poor indoor air quality (IAQ) in residential environments on children's respiratory health, the Nunavik's intervention study investigated the impact of the optimization of ventilation systems on the incidence rates of respiratory infections in children in Nunavik. Children under 10 years were recruited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Air pollution, particularly from anthropogenic activities, has been linked to a variety of health issues, especially respiratory problems. For instance, a study conducted in Nunavik showed that improving indoor air quality led to a decrease in respiratory infections in children [17]. While this study was conducted in a different context, it does highlight the potential health benefits of improving air quality.…”
Section: Introductionmentioning
confidence: 84%
“…Air pollution, particularly from anthropogenic activities, has been linked to a variety of health issues, especially respiratory problems. For instance, a study conducted in Nunavik showed that improving indoor air quality led to a decrease in respiratory infections in children [17]. While this study was conducted in a different context, it does highlight the potential health benefits of improving air quality.…”
Section: Introductionmentioning
confidence: 84%
“…, holes in floor, broken staircases). These conditions can place individuals at greater risk of infection by decreasing circulation of clean air within a home ( Poulin et al, 2022 ), and limiting control over risk mitigation (e.g., inadequate access to/control over kitchen or bathroom facilities; need for greater time spent in public spaces) ( Kamis et al, 2021 ; Soltan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%